FC 004PHOSPHATE FACILITATES PHOSPHATURIA BY PIT-2-MEDIATED ACTIVATION OF ERK1/2 SIGNALLING INTERNALIZING NAPI-2A FROM THE APICAL BRUSH BORDER MEMBRANE INDEPENDENT OF FGF23. (29th May 2021) - Walter, Stefanie; Vogt, Isabel; Schmitt, Roland; Haffner, Dieter; Leifheit-Nestler, Maren
Abstract: Background and Aims: Increased phosphate load stimulates the secretion of fibroblast growth factor (FGF) 23 in the bone leading to decreased phosphate reabsorption in the kidney. FGF23 activates FGFR1/Klotho/ERK1/2 signalling in proximal tubule cells to suppress type II sodium phosphate transporters NaPi-2a and NaPi-2c in the apical brush border membrane (BBM) resulting in lower serum phosphate levels. The type III sodium-dependent phosphate transporters PiT-1 and PiT-2 are expressed in key organs of phosphate regulation and were shown to activate ERK1/2 in osseous cells in the presence of high extracellular phosphate. Furthermore, PiT-2 was shown to be responsible for the phosphate-dependent FGF23 secretion in bone cells. Whether phosphate itself can be sensed by kidney cells and stimulate its own excretion remains unknown. The aim of our study was to examine the molecular mechanism regulating renal phosphate transport in the setting of chronic oral phosphate loading in mice and to analyse phosphate sensing as well as phosphaturic actions of phosphate itself independent of FGF23. Method: First, eight-week-old male C57BL/6 wildtype mice were fed a 2% high phosphate diet (HPD) or a 0.8% normal phosphate diet (NPD). Mice were sacrificed after six months and blood and urine were collected to determine parameters of phosphate homeostasis. Kidneys were isolated to evaluate the HPD-induced regulation of phosphate transporters by qPCR, immunoblot and histological analyses. Second, murine proximal tubule (mPT) cells were stimulated with either phosphate or FGF23 in the presence or absence of Foscarnet, as an inhibitor of phosphate transporters, to verify the molecular mechanism of phosphate sensing. Results: Although, HPD caused significantly elevated circulating levels of intact FGF23 which resulted in hyperphosphaturia, serum phosphate levels were still enhanced compared to NPD-fed mice. Renal Klotho protein expression was significantly reduced in HPD mice and histological staining demonstrated lower Klotho accumulation in proximal and distal tubule cells, while FGFR1 was not altered. The FGF23/Klotho/FGFR1 downstream pathway revealed neither a clear activation of the ERK1/2 signalling pathway nor induction of the transcription factor Egr-1 due to HPD. Nevertheless, NaPi-2a mRNA expression was significantly reduced in HPD-fed mice compared to NPD group and NaPi-2c was unchanged. The amount of NaPi-2a protein in isolated BBM vesicles of HPD-fed mice was lower compared to NPD and immunofluorescent staining confirmed the internalisation of NaPi-2a from the apical BBM. Among the type III sodium-dependent phosphate cotransporters, renal PiT-1 mRNA expression was not altered in HPD-fed mice, but PiT-2 was significantly increased compared to NPD group and immunofluorescent staining revealed an enhanced localization of PiT-2 on the basolateral membrane of proximal tubule cells. Stimulation of mPTs with phosphate or FGF23 increased the expression of PiT-2, induced the phosphorylation of ERK1/2 and decreased NaPi-2a in vitro . The pre-treatment with Foscarnet blunted the phosphate-mediated activation of ERK1/2 signalling pathway, but not the FGF23-induced effects, suggesting a direct phosphate transporter-regulating mechanism of high phosphate in renal proximal tubule cells. Conclusion: A chronic high dietary intake of phosphate results in downregulation of renal Klotho causing hyperphosphatemia, suggesting in part a renal resistance of FGF23/Klotho signalling pathway. However, HPD-induced internalization NaPi-2a from the apical BBM pointing to an FGF23-independent mechanism regulating phosphate reabsorption. Our data indicate that in the settings of high phosphate-mediated renal resistance of FGF23, phosphate itself may stimulate its urinary secretion via PiT-2-mediated activation of ERK1/2 signalling pathway which results in NaPi-2a downregulation and hyperphosphaturia independent of FGF23.